Evaluation of three dimensional modal pushover analysis for unsymmetric plan buildings subjected to two components of ground motion. - Reyes, Juan C. (Earthquake engineering & structural dynamics.)
The accuracy of the three dimensional modal pushover analysis (MPA) procedure in estimating seismic demands for unsymmetric plan buildings due to two horizontal components of ground motion, simultaneously, is evaluated. Eight low and medium rise structures were considered. Four intended to represent older buildings were designed according to 1985 Uniform Building Code, whereas four other designs intended to represent newer buildings were based on the 2006 International Building Code. The median seismic demands for these buildings to 39 two component ground motions, scaled to two intensity levels, were computed by MPA and nonlinear response history analysis (RHA), and then compared. Even for these ground motions that deform the buildings significantly into the inelastic range, MPA offers sufficient degree of accuracy. It is demonstrated that PMPA, a variant of the MPA procedure, for nonlinear systems is almost as accurate as the well known standard response spectrum analysis procedure is for linear systems. Thus, for practical applications, the PMPA procedure offers an attractive alternative to nonlinear RHA, whereby seismic demands can be estimated directly from the (elastic) design spectrum. In contrast, the nonlinear static procedure specified in the ASCE/SEI 41-06 Standard is demonstrated to grossly underestimate seismic demands for some of the unsymmetric plan buildings considered.